Pilot approach to analyzing patient and citizen involvement in health technology assessment in four diverse low- and middle-income countries. (25th January 2021) - Holtorf, Anke-Peggy; Mueller, Debjani; Sousa, M. Sharmila A.; Pretorius, Lauren; Wijaya, Kalman Emry; Adeyemi, Sylvester; Ankleshwaria, Dipen
Abstract: Background: In low- and middle-income countries (LMICs) striving to achieve universal health coverage, the involvement of different stakeholders in formal or informal ways in health technology assessment (HTA) must be culturally and socially relevant and acceptable. Challenges may be different from those seen in high-income countries. In this article, we aimed to pilot a questionnaire for uncovering the context-related aspects of patient and citizen involvement (PCI) in LMICs, collecting experiences encountered with PCI, and identifying opportunities for patients and citizens toward contributing to local decision- and policy-making processes related to health technologies. Methods: Through a collaborative, international multi-stakeholder initiative, a questionnaire was developed for describing each LMIC's healthcare system context and the emergence of opportunities for PCI relating to HTA. The questionnaire was piloted in the first set of countries (Brazil, Indonesia, Nigeria, and South Africa). Results: The questionnaire was successfully applied across four diverse LMICs, which are at different stages of using HTA to inform decision making. Only in Brazil, formal ways of PCI have been defined. In the other countries, there is informal influence that is contingent upon the engagement level of patient and citizen advocacy groups (PCAGs), usually strongest in areas such as HIV/AIDS, TB, oncology, or rare diseases. Conclusions: The questionnaire can be used to analyze the options for patients and citizens to participate in HTA or healthcare decision making. It will be rolled out to more LMICs to describe the requirements and opportunities for PCI in the context of LMICs and to identify possible routes and methodologies for devising a more systematic and formalized PCI in LMICs.